MULTIMEDIA STUDIES HELP US UNDERSTAND THE BENEFITS THE BENIFITS AND DRAWBACKS OF MASS MEDIA - Ahmedov Azimjon Ilhomovich the teacher of Andijan State Institute of Foreign Languages; Temirova Sevara, Maqsudaliyeva Nigina, Karimova Madina the student of Andijan State Institute of Foreign Languages, 311-group – English language; literature (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2023)
Abstract: The mass media are diversified media technologies which are intended to reach large audience by mass communication but technology varies based on the communication. Electronically information can be transmitted through broadcast media such as, film, television, radio and recorded music.